Miniaturization of multiband annular slot ring antenna using reactive loading. Issue 14 (22nd September 2018) - Mulla, Sajeed Sirajuddin; Deshpande, Shraddha S.
Abstract: A multiband annular slot ring (ASR) antenna for mobile communications is designed and analysed in this paper. Then, the miniaturized multiband ASR antenna loaded with distributed inductive stub is proposed, which is miniaturized by 20.28%. Another multiband ASR antenna loaded with meta-material (ASR-SRR) inspired Electromagnetically Coupled Split Ring Resonator (EC-SRR) is proposed, it is miniaturized by 30.55%. The surface wave of the proposed miniaturized ASR-SRR in higher mode has reduced due to increase in reactive impedance of the antenna surface, thus aperture efficiency is increased. The radiation characteristics of miniaturized antennas are approximately similar to the ASR antennas. Behaviour of antenna characteristics such as gain (G), impedance bandwidth (BW), aperture efficiency ( η A ), Chu condition ( ka ≤ 1) of proposed antenna is also studied, observed and analysed in this paper.